Factors that May Hinder the Implementation of the School-Wide Positive Behavior Intervention Support Model - Chitiyo, Jonathan; May, Michael E. (Journal of the American Academy of Special Education Professionals, 2018)
A growing body of research shows that the School-wide Positive Behavior Intervention Support model (SWPBIS) has the potential to reduce the occurrence of problem behavior in school settings, create positive school environments and enhance the academic outcomes of all students. However, although there is a growing body of research showing its efficacy, little is known about the challenges encountered when implementing the model. The purpose of this study was to determine the individual and environmental barriers that may hinder the implementation of SWPBIS. Results indicated that philosophical differences regarding SWPBIS and availability of resources were the main barriers to the implementation of SWPBIS. Recommendations are provided.